Quantum Black Holes in Conformal Dilaton–Higgs Gravity on Warped Spacetimes - Reinoud Jan Slagter (Universe, 2023)
A promising method for understanding the geometric properties of a spacetime in the vicinity of the horizon of a Kerr-like black hole can be developed by applying the antipodal boundary condition on the two opposite regions in the extended Penrose diagram. By considering a conformally invariant Lagrangian on a Randall–Sundrum warped five-dimensional spacetime, an exact vacuum solution is found, which can be interpreted as an instanton solution on the Riemannian counterpart spacetime, <semantics><msubsup>R+2</msubsup>×R1×S1</semantics>, where <semantics><msubsup>R+2</msubsup></semantics> is conformally flat. The antipodal identification, which comes with a CPT inversion, is par excellence, suitable when quantum mechanical effects, such as the evaporation of a black hole by Hawking radiation, are studied. Moreover, the black hole paradoxes could be solved. By applying the non-orientable Klein surface, embedded in <semantics>R4</semantics>, there is no need for instantaneous transport of information. Further, the gravitons become “hard” in the bulk, which means that the gravitational backreaction on the brane can be treated without the need for a firewall. By splitting the metric in a product <semantics>ω2<mover accent="true">g˜</mover>μν</semantics>, where <semantics>ω</semantics> represents a dilaton field and <semantics><mover accent="true">g˜</mover>μν</semantics> the conformally flat “un-physical” spacetime, one can better construct an effective Lagrangian in a quantum mechanical setting when one approaches the small-scale area. When a scalar field is included in the Lagrangian, a numerical solution is presented, where the interaction between <semantics>ω</semantics> and <semantics>Φ</semantics> is manifest. An estimate of the extra dimension could be obtained by measuring the elapsed traversal time of the Hawking particles on the Klein surface in the extra dimension. Close to the Planck scale, both <semantics>ω</semantics> and <semantics>Φ</semantics> can be treated as ordinary quantum fields. From the dilaton field equation, we obtain a mass term for the potential term in the Lagrangian, dependent on the size of the extra dimension.